Ceramic Coatings for High-Temperature Applications - Pakseresht, Amirhossein; Amirtharaj Mosas, Kamalan Kirubaharan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This edition includes sixteen publications covering various applications in the field of ceramic coatings. This Issue features ceramic coatings developed through plasma spraying, magnetron sputtering, and plasma-electrolytic oxidation. It is appropriate for graduate students, scientists, and engineers interested in corrosion and wear-resistant high-temperature coatings for industrial applications.